UPLC-ESI-MS/MS and Various Chromatographic Technique for Identification of Phytochemicals in Populus euphratica Oliv. Leaves Extract - Ezghayer, Mohammed A.; J. Kadhim, Enas (Iraqi Journal of Pharmaceutical Sciences, 2020)
The aim of this study is to screen the phytochemicals found in Populus euphratica leaves since this type of trees are used traditionally by many villagers as treatment for eczema and other skin disease and also this plant is poorly investigated for their phytochemicals especially in Iraq. Phytochemical screening of the extracts obtained from the n-hexane and chloroform fraction of leaves of Populus euphratica was done by Thin-layer chromatography and various spraying reagents to test if alkaloids, sterols and other compounds are present. UPLC-electrospray ionization –tandem mass spectroscopy along with GC-MS and HPTLC are used to identify the phytochemicals present in the plant leaves.UPLC-ESI-MS/MS method 20 compounds have been identified in various fractions among which are protopine alkaloids. salicin, salicortin, tremulacin. GC-MS showed that the observed data obtained are matched with that in NIST library and confirmed the presence of Hexadecanoic acid trimethylsilyl ester in 43.80% beta-Sitosterol in 37.14% and Diisooctyl phthalate 11.46%.UPLC-ESI-MS/MS is a powerful method for the identification of compounds in mixture based on comparison of their molecular, weight retention time and MS/MS fragmentation. Protopine alkaloid is identified for the first time in Populus euphratica and genus Populus. GC-MS is a valuable method for both qualification and quantification of various phytochemicals that are volatile in nature Keywords: Populus euphratica, GC-MS, phytochemical, UPLC-ESI-MS/MS